Purifikasi Tujuan Pendidikan Perspektif Ibn ‘Aṭā’illāh - Akmal Mundiri; Roihatus Sa'adah (Universitas Pesantren Tinggi Darul 'Ulum, 2018)
This research analyzes the goals of national education that have degenerated due to the problems of education that are increasingly complex. Therefore, purification of education goals is very needed to minimize the problems occur. This literature research examines the strands of wisdom of Sufism Ibn ‘Aṭā’illāh about how to achieve educational goals that emphasize the mystical riyāḍah without forgetting ikhtiyār ẓāhir. With the hope that educational goals can be achieved and solving educational problems. The main sources of this researching are by Ibn ‘Aṭā’illāh books relating to educational goals, especially al-Ḥikam, and other writers who discuss the problems of national education. This research concludes that, the educational goals of Ibn ‘Aṭā’illāh's perspective are to believe and fear Allah, noble, and do good deeds. There are formulations of educational goals are in three fields, namely individual goals, social goals, and professional goals.